Peran Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Dalam Mengatasi Kemiskinan - Hasan Jan, Radlyah; Hasan, Faradila; Janis, Budi (Forum Kerjasama Pendidikan Tinggi, 2023)
The problem of poverty is an issue that has existed for a long time and it can almost be said that it will remain an